Monitoring the endangered population of the antelope Kobus leche smithemani (Artiodactyla: Bovidae), in the Bangweulu ecosystem, Zambia - Victor M. Siamudaala; Musso Munyeme; Wigganson Matandiko; John B Muma; Hetron M Munang’andu (Revista de Biología Tropical, 2012)
Black lechwe (Kobus leche smithemani) is a semi-aquatic medium sized antelope currently enlisted on the IUCN red list of endangered species and is only endemic to the Bangweulu basin of Zambia. Its population has significantly decreased due to floods that took place during the period 1930-1940 from over 250 000-15 000 leading the Zambian government to gazette all habitats of Black lechwe into state protected areas, and to establish urgent management strategies needed to save the remaining population from extinction. Using retrospective data, our findings show that the population has increased from 15 000 animals in 1954 to 55 632 in 2009. The current population is estimated at 34.77% (55 632/160 000) of the carrying capacity of the Bangweulu basin. Although the Black lechwe is one of the 42 species offered for consumptive utilization by the Zambia Wildlife Authority (ZAWA), only 0.12% and 0.08% of the current stock was offered for safari and resident hunting annually for the period 2005-2009, respectively. Annual quota utilization were estimated at 67% (n=37) and 81% (n=37) for safari and resident hunting, respectively. Hence, overall income obtained from utilization of Black lechwe is very low accounting for only 2.1% of the total revenue earned from wildlife utilization. Although the current population trend is showing a unit increase of 639 animals per year, it is still far below levels ideal for the lucrative utilization. In this study, we demonstrate that adverse ecological changes on wildlife species, can lead to their vulnerability and danger of extinction, and that their recovery to full carrying capacity may demand a considerable amount of time El lechwe negro (Kobus leche smithemani) es un antílope semi-acuático de tamaño medio que en la actualidad se encuentra en la lista roja de la UICN de especies en peligro de extinción y sólo es endémica de la cuenca del Bangweulu de Zambia. Su población ha disminuido considerablemente, de más de 250 000 a 15 000, debido a las inundaciones que se dieron durante el período 1930-1940, lo que llevó al gobierno de Zambia a declarar todos los hábitats del lechwe negro en áreas protegidas estatales, y a establecer estrategias de administración urgentes necesarias para salvar el resto de la población de la extinción. Utilizando los datos retrospectivos, nuestros resultados muestran que la población ha aumentado de 15 000 animales en 1954 a 55 632 en 2009. La población actual se estima en 34.77% (55 632/160 000) de la capacidad de carga de la cuenca del Bangweulu. Aunque el lechwe Negro es una de las 42 especies que se ofrecen para su utilización consuntiva por la Autoridad de Vida Silvestre de Zambia (ZAWA), sólo el 0.12% y 0.08% de la población actual se ha ofrecido para el safari y la caza residente anual para el período 2005-2009, respectivamente. La utilización de la cuota anual se estima en 67% (n=67) y 81% (n=37) para safari de caza y residente, respectivamente. Por lo tanto, los ingresos totales obtenidos de la utilización del lechwe negro son muy bajos contando sólo el 2.1% de los ingresos totales obtenidos de la utilización de la fauna silvestre. Aunque la tendencia actual de la población está mostrando un incremento unitario de 639 animales por año, está todavía muy por debajo de los niveles ideales para la utilización lucrativa. En este estudio, se demuestra que los cambios ecológicos perjudiciales sobre especies de fauna silvestre, puede conducir a su vulnerabilidad y peligro de extinción, y que la recuperación de su capacidad de carga completa puede exigir una cantidad considerable de tiempo.